Mapping Urban Population Behavior in Using Private Transportation at City Center of Semarang. (August 2019) - Hanida, S L; Sejati, A W; Rakhmatulloh, A R; Rudiarto, I
Abstract: This paper aims to describe the identification of urban society behavior based on gender in using private transportation modes in the City Center of Semarang. The city center is the center of economic growth so that it has a high level of mobility and accessibility, especially in the use of private vehicles. This study uses GIS for Mapping and a quantitative approach to find out the most influential factors. The instrument uses a questionnaire and uses quantitative descriptive analysis techniques. The sample distributed was 100 respondents with an analysis unit, namely land use in the City Center such as trade and service areas, office centers, and government centers. The results of this study indicate that out of 100 research respondents, 66% were female gender. In addition, of the 11 variables used, only 5 variables have relevance; there area age, income, mode of transportation, ownership of the driving license, and commuter costs. From these variables found, one variable that most influences, which is the respondent's age, so it can be concluded that the dominant gender using private vehicles is women with productive age.